A Rare Case of Gorlin-Goltz Syndrome in Children - Fernanda Brasil Daura Jorge Boos Lima; Ana Paula Cota Viana; Luciano Henrique Ferreira Lima; Bruna Campos Ribeiro; Carlos Eduardo Assis Dutra; Glaykon Alex Vitti Stabile; Sergio Monteiro Lima Junior (Case Reports in Dentistry)
The Gorlin-Goltz syndrome, nevoid basal cell carcinoma syndrome, or basal cell nevus syndrome is an autosomal dominant condition disorder with high variability expression. It presents a series of relevant clinical manifestations that suggest its diagnosis in cutaneous, bone, dental, soft tissue, nervous, and ocular system disorders. This condition requires a great interaction of several specialists to improve the patient’s life. In this case, we presented a 9-year-old male patient referred to the Department of Oral and Maxillofacial Surgery reporting failure in the normal chronology of dental eruption. After evaluation, it was observed that the patient had 13 typical characteristics of the syndrome, including keratocysts, bifid ribs, palmoplantar pits, and 10 other minor characteristics. In conclusion, the expression of so many features of Gorlin-Goltz syndrome is rare in infants, and early diagnosis is important to decrease morbidity and mortality associated with basal cell carcinomas.